ANALISIS KINERJA TERHADAP WAKTU MENGGUNAKAN METODE EARNED VALUE ANALYSIS PADA PROYEK PEMBANGUNAN SMP N 7 KOTA BUKITTINGGI - Guciano, Ilham; Eka Priana, Surya; Herista, Febrimen (Ensiklopedia Research and Community Service Review, 2024)
In the implementation of the SMP N 7 Bukittinggi Development project, there was a delay in implementation which resulted in a minus deviation of work. Project success can usually be seen from the completion time and costs incurred without reducing the quality of the results. So it is necessary to conduct a Time and Cost Review research using the Earned Value Method on the SMP N 7 Bukittinggi Development Project. This research is quantitative research using Earned Value Analysis. The results of this study are the cumulative Schedule Variance (SV) value in week 1 is positive value of Rp. 11,816,608.92 this shows the performance of the project implementation in that week was carried out ahead of schedule. The cumulative SPI (Schedule Performance Index) in week 1 is worth 1 of 0.85, so the performance of project implementation is slower than planning. The estimated project completion time reviewed in week 10 obtained an EAS value of 309 days while the plan time was 180 days. This shows that the completion time is 129 days faster than planned if the project performance is in accordance with the plan or more than the plan. The estimated total project completion time is calculated based on the EAS value of 175 days while the plan time is 180 days. This shows that the completion time is 5 days faster than planned.Keywords: Time Schedule, Earned Value Analysis, SPI, ETS, EAS